2010
DOI: 10.1111/j.1939-0025.2010.01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Relations between social support and psychological and parental distress for lesbian, single heterosexual by choice, and two-parent heterosexual mothers.

Abstract: Relations between family type and psychological and parental distress and the moderating role of social support were studied for 90 Israeli lesbian mothers, single heterosexual mothers by choice and 2-parent heterosexual mothers who completed measures of psychological distress, well-being, parental distress, and direct and indirect social support. Findings indicated differences on psychological and parental outcome between mothers from the two heterosexual groups. Social support was higher for lesbian than sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 53 publications
2
46
0
1
Order By: Relevance
“…The analysis was completed using the SPSS AMOS statistical package, version 21 (IBM, Chicago, IL). The analysis was designed to control for demographic and socio‐economic differences between the WLP and LSAC samples, as these are factors that previous research has suggested may have an impact on psychological wellbeing: age of youngest child, number of children in household, gender of respondent, work status, income, education, and geographical area of residence (Kessler et al., ; Shechner et al., ).We used a complete case analysis to deal with missing data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis was completed using the SPSS AMOS statistical package, version 21 (IBM, Chicago, IL). The analysis was designed to control for demographic and socio‐economic differences between the WLP and LSAC samples, as these are factors that previous research has suggested may have an impact on psychological wellbeing: age of youngest child, number of children in household, gender of respondent, work status, income, education, and geographical area of residence (Kessler et al., ; Shechner et al., ).We used a complete case analysis to deal with missing data.…”
Section: Methodsmentioning
confidence: 99%
“…There is a prominent stream of public discourse criticising same‐sex relationships and positioning LGB parents as selfish, damaging or dangerous for children (Morse, McLaren & McLachlan, ). Fear of stigma or discrimination can lead parents to feel highly self‐conscious and anxious about their parenting (Di Lapi, ; Shapiro, Peterson & Stewart, ; Shechner, Slone, Meir & Kalish, , p. 283). Many lesbian mothers report that they feel pressure to consistently justify their parenting style and always perform ‘better than best’ to demonstrate their worth as a parent (Bos, van Balen & van den Boom, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Research has indicated that lesbian and gay parents are as competent and capable parents as are heterosexual parents (Patterson 2002; Shechner et al . 2010; Tasker 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Social Support or Social Networks. A social network is often used by parents to share information and resources (Shechner et al, 2010). Social networks may help individuals meet their daily accountabilities and overcome challenging situations by supplying them with emotional and instrumental support (Lin & Ensel, 1989).…”
Section: Family Of Originmentioning
confidence: 99%